Eugène Savitzkaya : une quête formelle pour savourer la vie - Teklik, Joanna (Wydawnictwo Naukowe UAM, 2013)
Savitzkaya, hardly known to French public, delights contemporary readers with his style, displaying both peculiar and variegated characteristics. Although he dispenses with the matters of genre, his latest texts (Célébration d’un mariage improbable et illimité, 2002, Exquise Louise, 2003, Fou trop poli, 2005) are still thought to represent the novel. His peculiarity lies in that he contrasts a daily routine with brilliantly worked form, nevertheless well suited to depict it. His predilection for language is pervasive in his style, showing strong preference for details (still, it stands in a stark contrast to the practice of the Nouveaux Romanciers of the 20th century). Savitzkaya asserts himself with the aid of conciseness, draws to a large extent upon surprising stylistic devices, juggles with words, even if paying careful attention to their precision. Finally, he acts as a genuine poet, reviving fragrances and colors of childhood. All in all, the whole of his work is designed to bring his readers to take pleasure in living.
Eugène Savitzkaya: formal experiments in an effort to make the most of life
Keywords: Belgium; contemporary novel; Savitzkaya; formal experiments